Morphologic indicators and harmful organisms associated to six Moringa oleifera origins under nursery and field conditions - Valenciaga, Nurys (Cuban Journal of Agricultural Science, 2024)
In order to monitor the morphologic indicators and the organisms caused of plagues associated to Moringa oleifera two tests were conducted: nursery and field. The treatments were represented by six moringa origin, collected in three provinces of the country. In nursery, a total of 396 polyethylene bags were used in a completely random design, with 66 repetitions. In field, a random block design with three replications was applied. In both test the arthropods and associated pathogens were monitoring. The phytosanitary damage and morphologic indicators of the crop growing were evaluated. In nursery phase, the plants did not have economic damages by harmful organisms and showed favorable grow indicators. Therefore, in field, the new transplant plantlets were affected by strong attacks of Atta insularis, which caused defoliation and plantlets loss. The survival has similar average ranges in all origins. The count of branches was better in the origins 4 and 6 with 4.40 and 4.18, respectively. The height, at 120 days after the transplant, showed sizes higher than 145 cm, in the origins 2 and 6. The higher stem thickness (31.2 mm) was showed in the origin 2. It is concluded that the evaluated origins, according to their morphologic indicators performance have potentialities for their use. It is recommended to continue with the phytosanitary alertness of the crop and to regulate the forage activity of A. insularis until achieving the moringa establishment. It should be alert in the fruiting phase of the incidence of Gitona sp. fly to minimize the damage to the seeds, to avoid the secondary presence of pathogens and to allow the harvest of healthy seeds.